(untitled) (Global Journal of Management and Business Research, 2021)
What is Ethnography: Ethnography is rese arch, precisely about individuals, societies and their culture. It aims to study social and cultural aspects of society and the researcher focuses to collect information for that. It focuses on the behaviour of people concerning the social setup they live in. The outcome of a field study mirrors the learning and the arrangement of implications in the lives of a social gathering. De partment of Anthropology, Princeton University defines Ethnography as #x201C;a research method central to knowing the world from the standpoint of its social arrangements.